PERANCANGAN LOGO DAN MEDIA PROMOSI PT AMERTA SARI TRANSPORT SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Santika, Gede Danu Arya; Fianto, Achmad Yanu Alif; Aziz, Abdul (Jurnal ArtNouveau, 2013)
Amerta Sari Transport known as AS TRANS, is logistic transport specialized handling industrial distribution across islands trough Java and Bali. But, not all potentials logistic transport management and promotedÂ  by innovative and creative concept, especially for branding new product to public. So, there are not many people knows the potential of AS TRANS Logistic. The goal of design to find out how to Designing Media Campaign of AS TRANS as an effort to mount Brand Awareness. The design is done with a qualitative approach, namely observation, deep interviews, content analysis and study exist in order to formulate a design concept. The data were analyzed research process dan understands and investigating social phenomena and people troubles with focus on real connection between researcher and subject research (Noor,2011:32). From the analysis, it was found that the uniqueness by AS TRANS has not fully lifted to a wide audience. Lack of promotional efforts and unknown Brand Identities to be one of the obstacles that make the brand potential has not been known. After going through the process of data analysis, found the keyword or concept design âDinamicâ its mean the person who had spirit, energy, self supporting and adaptable. In this case âDinamicâ described that put the needs and expectation of dynamic modern society, which the need of society that living a fully effective, efficient, fast and reliable. Fast strengthen the concept of satisfying customers. Where the audiens given stylish visual appearance of fantastical, imaginative thinking trough impossible things and is asked to actively and aggressive communication. The result are expected to raise some of the customers awareness of product AS TRANS Logistics.